1998
DOI: 10.1109/16.711351
|View full text |Cite
|
Sign up to set email alerts
|

Off-state breakdown in power pHEMTs: the impact of the source

Abstract: Abstract-Conventional wisdom suggests that in pseudomorphic high electron mobility transistors (pHEMT's), the field between the drain and the gate determines off-state breakdown, and that the drain to gate voltage therefore sets the breakdown voltage of the device. Thus, the two terminal breakdown voltage is a widely used figure of merit, and most models for breakdown focus on the depletion region in the gate-drain gap, while altogether ignoring the source. We present extensive new measurements and simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This provides experimental evidence to support an earlier interpretation. 15 In conclusion, we have demonstrated that a thermally activated surface hopping conduction mechanism can control the breakdown characteristics of AlGaN/GaN HFETs at lower fields than that at which avalanche multiplication is expected. This leakage mechanism has an activation energy of 0.21 eV and is sensitive to the method of surface preparation.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…This provides experimental evidence to support an earlier interpretation. 15 In conclusion, we have demonstrated that a thermally activated surface hopping conduction mechanism can control the breakdown characteristics of AlGaN/GaN HFETs at lower fields than that at which avalanche multiplication is expected. This leakage mechanism has an activation energy of 0.21 eV and is sensitive to the method of surface preparation.…”
mentioning
confidence: 68%
“…The gate leakage current, I g , beyond pinchoff was measured as a function of the temperature using two-terminal measurements between the gate and drain ͑with the source floating͒ to eliminate effects due to channel current. 15 Figure 2 shows the temperature dependence of I g and the breakdown voltage from 20 to 200°C, which show a positive and a negative temperature coefficient, respectively. To ensure that true breakdown voltage dependence was observed, several devices were biased to destruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 The gate current was measured as a function of gate-drain voltage both with fixed gate-source voltages and with the source floating in order to investigate the influence of the source on the leakage in the gate-drain diode. 6 Data were obtained for temperatures ranging from 175 to 500 K, as measurement of temperature-dependent current-voltage characteristics allowed a more detailed analysis of each leakage mechanism to be performed. Additionally, one-and two-dimensional numerical simulations were performed to estimate the magnitudes of the electric fields directly under the gate and at the drain-side edge of the gate contact.…”
Section: Methodsmentioning
confidence: 99%
“…The breakdown voltage is marked by a sharp increase in the gate/drain current [19,20] and is defined by a direct measurement, where the negative gate current (I g ) reaches a magnitude of 1 mA/ mm. The increase in I g is due to minority carriers (holes), which are generated by the impact ionization process.…”
Section: Resultsmentioning
confidence: 99%